A Design of English Immersion Camp for Supplementing English Teaching and Learning in Indonesia - Ummu Syahidah; Faujia Umasugi; Zakiah Buamona (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The primary purpose of this study is to design a supplementary English learning program for English students in Muhammadiyah University of North Maluku called UMMU English Immersion Camp (UEIC). Three kinds of instruments were used to gather the data, which encompassed open-ended questionnaire, UEIC observations, and interviews. To design the program, data from questionnaire were obtained from the participants which was part of Needs Analysis before conducting the UEIC. Observations and Interviews were done during the UEIC. The Results conveyed that The UEIC participants needed English learning programs that can develop and improve their ability to communicate in English confidently and in the right way. The UEIC design tried to cover the participants’ needs by fomulating an English learning program where the goal was “to develop participants’ communicative competence”. The objectives were (1) to provide English environment where participants can practice their English ability in context, (2) to trigger participants to be more active and be confident in expressing their thought using English, and (3) to create participants’ togetherness and stimulate participants ability to work in group.